POSSIBILITY OF USING CLAY-BASED BARRIER MATERIALS FOR LOCALIZING THE CONSEQUENCES OF RADIATIONS ACCIDENTS (FOR EXAMPLE, THE FUKUSHIMA DAIICHI NPP) - Mikhail V. Antonenko; Evgeny V. Bespala; Vyacheslav F. Myshkin; Alexander O. Pavlyuk; Sergey G. Kotlyarevskiy; Elena V. Zakharova; Anna G. Volkova; Yuliya R. Bespala (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
The relevance of the research topic is caused by the need to develop new innovative barrier materials with anti-filtration and anti-migratory properties to localize the consequences of the disaster at the Fukushima Daiichi NPP. The main aim of the study is the review of the possibility of using domestic technologies for localization of radionuclides inside the points of placement of radioactive waste and nuclear materials (corium) to solve the problem of migration of radionuclides at the Fukushima-Daiichi NPP. Methods: mathematical modeling of radionuclides migration from the active zone of the destroyed power units of the Fukushima Daiichi NPP through clay-containing safety barriers. The results. The paper presents the results of consideration of possibility of using barrier materials for localizing the consequences of radiations accidents. Using the safety clay-based barriers and gelling solutions to prevent the underground migration of radionuclides from destroyed power units to environment was suggested according to positive domestic experience. Accident on nuclear power plant Fukushima-1, occurred on 11 March 2011, was chosen as an example of such a situation. Currently this object is the area for working out the technology and approaches to eliminate the radiation accidents. It was shown that the inflow of radioactive contamination into the ocean is caused by groundwater, rainwater and cooling water, which is daily pumped into the damaged core. Disadvantages of the system used by the safety barrier based on ground frosts were described. On the basis of positive domestic experience, the use of clay-containing safety barriers was proposed to prevent migration of radionuclides from destroyed power units to the ocean. Clay-content materials based on vermiculite, perlite, zeolite, schungite and their sorption characteristics were determined for these purposes. The results of modeling the migration of the most active radionuclides (Pu, Cs, Sr, U) through the described barrier materials were presented. The possibility of using the safety barrier based on a mixture of clays was shown. The width of such a barrier does not exceed 3,7 m (determined by the rate of migration of uranium). The total volume of clay-based material barrier required to prevent migration of radionuclides is ~145900 m3.